Topological Dimension - Azram, Mohammad (University of Peshawar, 2010)
In this article we will establish some basic but pivotal results regarding dimension of spaces with relative topologies. Most of the results are known to the readers but we have established their generalization through a simple variational approach. In the creative process, focus has been on well defined simple concepts as an expeditious means of involving mathematics loving students in research. We have established that any subset A of ε1 with dense Ac of ε1 is of 0-dimension. Using inductive approach, we have proved that dimension is in fact a topological invariant.